Pelatihan Asertif untuk Menurunkan Perilaku Cyberbullying - Rima Nur Hidayati; Muhammad Novvaliant Filsuf Tasaufi (Bandung Conference Series: Psychology Science, 2022)
Abstract. Mental health has an important meaning for human life. Mental health is currently influenced by the development of internet access, especially the use of social media. One of the negative impacts of using social media on mental health in adolescents that must be watched out for is cyberbullying. One of the main characteristics of cyberbullying victims is someone who has not been able to be assertive. Interventions that are often used to reduce cyberbullying are using assertive training. This study uses a literature review method to look at various studies regarding the use of assertive training in reducing cyberbullying behavior. Based on the results of a literature review, assertive training has proven effective in reducing cyberbullying behavior. Abstrak. Kesehatan mental memiliki arti penting bagi kehidupan manusia. Kesehatan mental saat ini dipengaruhi oleh perkembangan akses internet terutama penggunaan media sosial. Salah satu dampak negatif dari penggunaan media sosial terhadap kesehatan mental pada remaja yang harus diwaspadai adalah cyberbullying. Salah satu karakteristik utama korban cyberbullying adalah seseorang yang belum mampu bersikap asertif. Intervensi yang sering digunakan untuk menurunkan cyberbullying adalah dengan menggunakan pelatihan asertif. Penelitian ini menggunakan metode kajian pustaka untuk melihat berbagai penelitian mengenai penggunaan pelatihan asertif dalam menurunkan perilaku cyberbullying Berdasarkan hasil dari kajian pustaka, pelatihan asertif terbukti efektif dalam menurunkan perilaku cyberbullying.